2016
DOI: 10.1002/ece3.1985
|View full text |Cite
|
Sign up to set email alerts
|

Birth dates vary with fixed and dynamic maternal features, offspring sex, and extreme climatic events in a high‐latitude marine mammal

Abstract: Reproductive synchrony tends to be widespread in diverse species of plants and animals, especially at higher latitudes. However, for long‐lived mammals, birth dates for different individuals can vary by weeks within a population. A mother's birth timing can reveal useful information about her reproductive abilities and have important implications for the characteristics and survival of her offspring. Despite this, our current knowledge of factors associated with variation in birth dates is modest. We used long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 79 publications
(274 reference statements)
4
49
1
Order By: Relevance
“…; Rotella et al. ). Weddell seals are probably the best studied of all pinnipeds, at least regarding its natural history and demography.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…; Rotella et al. ). Weddell seals are probably the best studied of all pinnipeds, at least regarding its natural history and demography.…”
Section: Introductionmentioning
confidence: 98%
“…The southernmost breeding population of mammals in the world is the Weddell seal (Leptonychotes weddellii) in McMurdo Sound, Ross Sea, a population involved in continuous mark-resight studies since the late 1960s (Stirling 1969;Siniff et al 1977;Testa and Siniff 1987;Cameron and Siniff 2004;Garrott et al 2012;Rotella et al 2016). Weddell seals are probably the best studied of all pinnipeds, at least regarding its natural history and demography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much contemporary research on birth timing has tested for effects of these factors with implications that climate conditions, food availability, status, disease or contaminant loads directly or indirectly affect maternal body condition (e.g., Gilmartin et al 1976;Skogland 1984;Rachlow and Bowyer 1991;Lunn and Boyd 1993;Bowen et al 2003). Additionally, climate conditions and food availability can influence the growth of a developing fetus and whether or not the mother skips a year of giving birth, which in turn, have been correlated with subsequent parturition date (Drickamer 1974; Rotella et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic factors that play a role can include age, body size, and previous reproductive history (e.g. Lunn et al 1994, Plard et al 2014, Rotella et al 2016. For example, Plard et al (2014) showed that parturition date in roe deer was negatively related to adult quality (measured as median body mass) and age.…”
Section: Introductionmentioning
confidence: 99%